2001
DOI: 10.1109/6144.926396
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of soldered joints in CSPs of various designs and mounting conditions

Abstract: The chip size package (CSP) is being used in various portable electronic products recently. Further evaluation of the reliability of its soldered joints is required all the more now because those soldered joints are invisible. This study focused on the thermal fatigue life of soldered joints in the CSP. CSPs were mounted on printed circuit boards (PCBs) in various configurations and mounting conditions, and underwent thermal cycle testing. Then, the fatigue lives of their soldered joints were compared.As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Differing from soldered joints in conventional packages, such as Quad Flat Packages (QFPs), the small ball‐shaped joints in CSPs cannot be inspected directly (Kariya et al , 1999). Hence, investigations into the reliability of solder joints in CSPs are extremely difficult (Sumikawa et al , 2001). As a matter of fact, very few studies on the reliability of CSP solder joints can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Differing from soldered joints in conventional packages, such as Quad Flat Packages (QFPs), the small ball‐shaped joints in CSPs cannot be inspected directly (Kariya et al , 1999). Hence, investigations into the reliability of solder joints in CSPs are extremely difficult (Sumikawa et al , 2001). As a matter of fact, very few studies on the reliability of CSP solder joints can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is currently being developed for fine pitch technology, high density, high precision and multifunction. [3][4][5][6] The 63A solder alloy powder is applied largely in SMT. In order to satisfy the SMT requirement, there are two important parameters for the 63A solder powders: the shape and the diameter of the particle.…”
Section: Introductionmentioning
confidence: 99%
“…The thicker the layer is, at a given thermal expansion mismatch, the lower is the shear plane angle and the inclination to formation of cracks. This is well known from reliability investigations of solder joints e.g., between chip components and PCBs where it was found that the number of thermal cycles until failure increases significantly with rising stand-off height [57].…”
Section: Ica For Interconnecting Parts With Dissimilar Thermal Expansmentioning
confidence: 97%